2007
DOI: 10.1111/j.1600-0609.2007.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

CD44 and hyaluronan engagement promotes dexamethasone resistance in human myeloma cells

Abstract: Dexamethasone (Dex) is an effective therapeutic agent against multiple myeloma (MM); however, resistance to it often becomes a clinical issue. CD44 is an adhesion molecule that serves as a cell surface receptor for extracellular matrix components, including hyaluronan (HA). HA is an extracellular matrix component that is involved in survival and progression in MM. In the present report, we describe isolation of a CD44-expressing population from a Dex-sensitive MM cell line, RPMI8226, in which the CD44-high pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…This result is in line with the analysis of the CD44 null mutant mice, which, surprisingly, do not reveal major developmental defects (Protin et al, 1999). Although previous studies have demonstrated that in in vitro cellular systems hyaluronan provides cells with apoptotic protection via the interaction with hyaluronan receptor CD44 (Kaneko et al, 2000;Ozeki et al, 2001;Ohwada et al, 2008), our findings seem to point out that in a more complex in vivo system, other hyaluronan receptors might compensate for CD44 depletion (Nedvetzki et al, 2004). In this respect, it is important to note that RHAMM, another hyaluronan receptor, is expressed in cranial NCC during Xenopus development (Casini et al, 2010).…”
Section: Discussionmentioning
confidence: 50%
“…This result is in line with the analysis of the CD44 null mutant mice, which, surprisingly, do not reveal major developmental defects (Protin et al, 1999). Although previous studies have demonstrated that in in vitro cellular systems hyaluronan provides cells with apoptotic protection via the interaction with hyaluronan receptor CD44 (Kaneko et al, 2000;Ozeki et al, 2001;Ohwada et al, 2008), our findings seem to point out that in a more complex in vivo system, other hyaluronan receptors might compensate for CD44 depletion (Nedvetzki et al, 2004). In this respect, it is important to note that RHAMM, another hyaluronan receptor, is expressed in cranial NCC during Xenopus development (Casini et al, 2010).…”
Section: Discussionmentioning
confidence: 50%
“…The expression of these class of markers has been shown to be intrinsically related to different PC chemoresistant potential in vitro and in vivo, [40][41][42][43][44][45] as well as to patients' survival, [46][47][48] which would be potentially due to a stronger attachment of MRD clonal PCs to the BM stroma, which provides higher protection from 49,50 In fact, it could be hypothesized that a subset of chemoresistant MRD cells strongly attached to the stroma might be potentially underestimated in BM aspirates. By contrast, a different role has been assigned to CD44 in cell adhesion-mediated drug resistance in several cancers including MM, where CD44 may partially contribute to dexamethasone resistance 51 and becomes upregulated in lenalidomide-resistant MM cells to stabilize the expression of P-glycoprotein, a multidrug resistance efflux pump responsible for the cellular uptake of lenalidomide. 13,52 Interestingly, differences between diagnostic vs MRD cells were more pronounced among patients treated only with VMP vs cases exposed to VMP and Rd.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in MM, treatment success of Dexamethasone was dependent on CD44 with decreased apoptosis rates in cells with high CD44 [148]. Here neutralizing CD44 might reveal new therapeutic strategies in treatment of multidrug resistant haematological malignancies.…”
Section: Experimental Antagonization and Drug Resistancementioning
confidence: 90%